STONE AGE SETTLEMENTS OF UZBEKISTAN - N.U.Xolmatov; M.G’aniev (Galaxy International Interdisciplinary Research Journal, 2022)
The history of personality in the knowledge of the daily lifestyle, social system, economic activities of the communities of the Stone Age, the settlements in which they live also play an important role as a source of information. In fact, in the early stages of the development of the history of personality, primitive communities used natural habitats, in particular caves, elevations, tree tops, pits, as settlements. Since primitive communities were engaged in farming and hunting in the early stages of their development, their habitat often acquired a short-term character. However, studies have found that some multi-cultural layered caves are long-term settlements. On the Central Asian scale, it is considered from the sentence g’cave spaces such as flood-Ungur, Obi-Rahmat, Jabal, Dam-rest-Fountain 1.2, open-ended. Primitive people over time blocked the cave, the front part of the ungyrs, artificially, in addition, from cold winds, rain, snow, Shakh-shakhba, animal skins. cave spaces have recovered field levels(sticks) in front of the mouth section. In this way, people built their own settlements. They were in the form of a semi-basement, a basement, and in the last Paleolithic survey of Samarkand, information about this was obtained.